Cambodian Refugee Families: Impacts of Immigration-Related Stressors on Intergenerational Relationships. Issue 2 (3rd April 2017) - Muruthi, James R.; Lewis, Denise C.
ABSTRACT: The purpose of this study was to elucidate Cambodian refugees' perceptions of immigration-related stressors and their impacts on intergenerational relations during the processes of immigration and settlement. We used narrative analysis to evoke older immigrants' voices as they transitioned to the United States. Thirty-one Cambodian immigrants were interviewed using open-ended interview guides informed by ethnographic tenets of data collection. Participants expressed (a) changes in family structure and elder isolation and (b) intergenerational ambivalence and elder's dependence on adult children as products of immigration-related stressors. Implications of these results for refugee and immigrant mental health research are discussed.